Sedimentology of the shallow marine deposits of the Calafate Formation during the Maastrichtian transgression at Lago Argentino, Austral-Magallanes Basin, Argentina (Latin American Journal of Sedimentology and Basin Analysis, 2021)
The Maastrichtian shallow marine deposits exposed at the south margin of the Lago Argentino within the Austral-Magallanes Basin are known as the Calafate Formation. In order to interpret the depositional systems and reconstruct the sequence stratigraphic architecture for this unit at its type locality (Cerro Calafate), we acquire new data from seven stratigraphic sections. We recognized six facies associations (FA-1 to FA-6) corresponding to shallow marine deposits, which are organized vertically displaying a transition from shallower to deeper conditions, representing a ~90 m thick transgressive succession. The Calafate Formation deposits are differentiated into a lower wave-dominated coast (FA1, FA2 and FA3) and an upper tide-dominated coast (FA4, FA5 and FA6), each marked by the dominance of wave and tidal sedimentary processes, respectively. The Calafate Formation overlies the fluvial deposits of the Chorrillo Formation by a transgressive surface (TS), which is overlaid by a transgressive marine succession characterized by a retrogradational stacking pattern. The latter is finally covered by offshore transition marine deposits marking a progressive deepening of the depositional system that culminates with the maximum flooding surface (MFS). From here, an aggradational stacking pattern dominates the upper sandstones of the unit representing the highstand systems tract (HST), which is interpreted to be the cause of short-term periods when the accommodation space rate was nearly equaled to the sediment supply rate during the Maastrichtian.